2020
DOI: 10.34117/bjdv6n4-170
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento, biomassa e qualidade fisiológica do arroz em função da aplicação foliarde silício

Abstract: Crescimento, biomassa e qualidade fisiológica do arroz em função da aplicação foliarde silício Growth, biomass and physiological quality of rice as a function of foliar application of silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
4
5
0
4
Order By: Relevance
“…Still regarding shoot development, studies performed with other plant groups also showed increased plant height, such as for rice (Zanetti et al, 2016;Couto et al, 2020), passion fruit (Costa et al, 2016), potato (Soratto et al, 2019), peanut (Dong et al, 2018), sunflower (Flores et al, 2018b), and tomatoes when not subjected to water stress (Moraes et al, 2020). Therefore, evidence demonstrates that for this parameter Si is highly responsive, and can be an alternative resource for plant development, especially for foliar application, as evidenced by the present study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Still regarding shoot development, studies performed with other plant groups also showed increased plant height, such as for rice (Zanetti et al, 2016;Couto et al, 2020), passion fruit (Costa et al, 2016), potato (Soratto et al, 2019), peanut (Dong et al, 2018), sunflower (Flores et al, 2018b), and tomatoes when not subjected to water stress (Moraes et al, 2020). Therefore, evidence demonstrates that for this parameter Si is highly responsive, and can be an alternative resource for plant development, especially for foliar application, as evidenced by the present study.…”
Section: Discussionsupporting
confidence: 71%
“…Another important feature is its ability to accumulate silicon (Si) (Epstein, 2009). Although studies on Si for this crop are incipient, its application has shown promising results, increasing yield when applied to Si-accumulating plants such as rice (Couto et al, 2020), sugarcane , maize (Oliveira et al, 2020a), sorghum (Flores et al, 2018a;Oliveira et al, 2020a), sunflower (Flores et al, 2018b;Peixoto et al, 2020), industrial processing tomato (Moraes et al, 2020), and wheat (Qamar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in Si by plants does not have a direct relationship with the production of biomass and it not considered an essential element for the plant cycle, however the results of its use can be satisfactory or because a decrease in development according to the quantity adopted. According to Couto et al (2020), utilization showed efficiency with maximum estimated dose for application in rice of 1.68 g L -1 , using sodium and potassium silicate stabilized with sorbitol as a source. Positive results, through the application of Si, also reported in the productive performance and in the post-harvest of cauliflower (BARRETO et al, 2017;CURVELO et al, 2019;HOSSAIN et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Couto et al (2020) avaliaram a aplicação de silício via foliar no crescimento, biomassa e qualidade fisiológica do arroz. Nesse ensaio foi feita a aplicação de doses crescentes de silicato de sódio e potássio os autores observaram que a qualidade fisiológica das plantas de arroz não é afetada pela aplicação de silício e foi observado que com a aplicação da dose superior a 1,68 g L -1 há uma redução no aproveitamento do silício pela planta Oliveira et al (2020).…”
unclassified